Frogs, Toads, and Bats Oh My! Population Surveys of Frogs, Toads, and Bats on Islands of the Chippewa River - Meyer, Breana; Schoen, John; Wojan, Christopher (My University, 2013)
The purpose of this study was to determine which species of anurans (frogs and toads) and bats occupy or use islands of the Chippewa River in west-central Wisconsin.
Color poster with images, photographs, and graphs.
Keywords: Island ecology--Habitat--Research; Islands--Wisconsin--Chippewa River; Anurans--Population surveys; Bats--Population surveys; Posters